Trends of terrestrial water storage and actual evapotranspiration in Chinese inland basins and their main affecting factors - Liu, Xuan; Liu, Zhaofei; Wei, Haoshan (Frontiers in Environmental Science, 2022)
The Chinese inland basins (CIBs) are vulnerable to global warming and human activities due to low precipitation and high potential evaporation. Terrestrial water storage (TWS) is an important component of the hydrological cycle and essential for evaluating the water resource security of the CIBs. Although some studies have focused on water storage trends in sub-basins of the CIBs, only few studies have analyzed water storage trends in the CIBs as a whole. In this study, trends and magnitudes of precipitation, TWS, and actual evapotranspiration (AET) were detected by the rank-based non-parametric Mann–Kendall test and trend magnitude method. Based on the hydrological budget of the closed inland basin, the monthly series of AET were simulated and the main factors affecting TWS changes in the CIBs and each closed basin were identified. Results showed that both precipitation and AET significantly increased in the CIBs. Precipitation decreased from the northwest and southeast regions to the central region in the CIBs. Moreover, the annual TWS in the CIBs significantly decreased mainly due to the increased AET. Approximately 60% AET increase was attributed to increased irrigation diversions. At the basin scale, similar to the CIBs, changes in AET were the predominant factor influencing changes in TWS in the Tarim basin (TRB), Turpan basin (TPB), and Hexi Corridor basin (HCB). Qiangtang Plateau basin (QPB) Qaidam basin (QDB) the increase in precipitation contributed more than 60% increase in TWS glacier melting and irrigation diversion.